The Structure of the Synaptic Vesicle-Plasma Membrane Interface Constrains SNARE Models of Rapid, Synchronous Exocytosis at Nerve Terminals - Gundersen, Cameron B. (Frontiers in Molecular Neuroscience, 2017)
Contemporary models of neurotransmitter release invoke direct or indirect interactions between the Ca2+ sensor, synaptotagmin, and the incompletely zippered SNARE (soluble, N-ethyl-maleimide-sensitive factor attachment protein receptor) complex. However, recent electron microscopic investigations have raised pragmatic issues concerning the mechanism by which SNAREs trigger membrane fusion at nerve terminals. The first issue is related to the finding that the area of contact between a “fully primed” synaptic vesicle and the plasma membrane can exceed 600 square nm. ~4,000 lipid molecules can inhabit this contact zone. Thus, renewed efforts will be needed to explain how the zippering of as few as two SNARE complexes mobilizes these lipids to achieve membrane fusion. The second issue emerges from the finding that “docking filaments” are sandwiched within the area of vesicle-plasma membrane contact. It is challenging to reconcile the location of these filaments with SNARE models of exocytosis. Instead, this commentary outlines how these data are more compatible with a model in which a cluster of synaptotagmins catalyzes exocytotic membrane fusion.